Preparedness for maternal and neonatal emergencies in UK midwifery units: a national survey using the UK Midwifery Study System (UKMidSS) - Meroz, MR; Yu, L-M; Sanders, J; Rowe, R (Elsevier, 2022)
Objective We aimed to document and describe variation in a range of factors impacting on preparedness for and the management of emergencies in midwifery units in the UK. Design, setting and participants National cross-sectional survey administered online through the UK Midwifery Study System (UKMidSS) to midwife ‘reporters’ in all 206 alongside and freestanding midwifery units in the UK, January-April 2020. Topics investigated included communication with the ambulance service in freestanding units, staff support for emergencies, training and equipment held. Findings In total, 137 (67%) midwifery units responded, representing 75% of eligible UK maternity services. There was no evidence of differences between responding and non-responding units in terms of type of unit, annual number of births, or country/region of the UK. Overall, 10 freestanding units (20%) reported using an ordered categorical system (e.g. ‘category 1’ or ‘code red’) to communicate an emergency to the ambulance service, 17 (35%) reported using other words describing urgency (e.g. ‘obstetric emergency’), and 15 (31%) reported having no agreed word or phrase. Almost all alongside units reported that a senior midwife, paediatrician/neonatologist and obstetrician might attend in an emergency, whereas most freestanding units reported the attendance of paramedics and/or a senior midwife. The type and frequency of staff training varied, with 77% of units reporting annual skills and drills training, and lower proportions reporting annual multi-disciplinary simulation (55%), in-situ simulation (50%) and neonatal life support training (59%). The equipment kept in midwifery units varied between different types of unit. For example, 28 alongside units (32%) reported keeping ventouse in the unit and 21 (24%) kept forceps, compared with 4 (8%) and 2 (4%) freestanding units respectively. Almost half of freestanding units (47%) and around a quarter of alongside units (24%) reported having a cardiotocograph (CTG) in the unit. Conclusions The study found wide variation in factors that impact on preparedness for and management of emergencies in UK midwifery units. Although some variation is inevitable given the varying size and location of units, this study has identified some areas where greater consistency might improve outcomes.